2004
DOI: 10.1068/a35230
|View full text |Cite
|
Sign up to set email alerts
|

Gender Struggle, Scale, and the Production of Place in the Appalachian Coalfields

Abstract: IntroductionEvelyn is a woman in her forties who has lived her entire life in the Appalachian coalfield community of McKee County, Kentucky. (This is a pseudonym as are all the names in the paper.) Like many women in the region, she married a miner in her teens and was a mother and wife for almost twenty years. She did not work outside the home during those years. Today, however, she is divorced, is working toward an Associate's Degree in business; and is the owner of a small antique store. When asked about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…2. Tensions between city and country, local and global, as well as past and future are evident in respondents' definition of the 'Heartland' not just as a policy or a locale, but also as a place to live, work, and play (Miewald and McCann, 2004). Each group struggled to write its own definition of 'the Heartland' onto the study area.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…2. Tensions between city and country, local and global, as well as past and future are evident in respondents' definition of the 'Heartland' not just as a policy or a locale, but also as a place to live, work, and play (Miewald and McCann, 2004). Each group struggled to write its own definition of 'the Heartland' onto the study area.…”
Section: Discussionmentioning
confidence: 93%
“…Despite difference in terms, both refer to place as a location in which daily activity occurs. Finally, place is a complex interaction of ''attachment to social memory, identity, and sense of place'' (Miewald andMcCann, 2004, p. 1047). This third aspect of place is process-related and has to do with how individuals and groups become attached to particular perceptions of what 'should' or 'ought' to occur somewhere.…”
Section: The Meaning and Politics Of Placementioning
confidence: 97%
See 2 more Smart Citations
“…Heather, Skillen, Young, and Vladicka (2005) focusing on the social reproduction of patriarchal subjectivities in rural communities mapped women's triple responsibility for the survival of farm, family, and community, accentuated by agricultural and health care restructuring in Alberta. Similarly, American research by Miewald and McCann (2004) documented the impact of the declining male-dominated mining industry in the Appalachian coalfields, and the increase in femaledominated service jobs, which produced a series of struggles between men and women over appropriate gender roles relating to waged work and household work, in turn, negatively influencing social relations. Leach's (2009) research in Ontario's North Wellington County showed that despite first holding and then losing similar jobs in manufacturing, men and women had different experiences and outcomes following the rural economic restructuring.…”
mentioning
confidence: 99%